Liability Dollarization and the Bank Balance Sheet Channel - Cook, David (IMF Working Papers; Working Paper, 2002)
Banks in developing economies often face a mismatch in the currency denomination of their liabilities (foreign currency denominated debt) and assets (domestic currency loans to domestic borrowers). We study the effect of this mismatch on business cycles and monetary policy in a sticky-price, dynamic general equilibrium model of a small open economy. We find from the model analysis that a fixed exchange rate rule that stabilizes the balance sheets of banks offers greater stability than an interest rate rule that targets inflation in the sticky-price sector of the economy.